2001
DOI: 10.1007/s002680020043
|View full text |Cite
|
Sign up to set email alerts
|

Factors Predicting Nutritional Derangements in Patients with Obstructive Jaundice: Multivariate Analysis

Abstract: Patients with obstructive jaundice (OJ) that requires surgery often have malnutrition associated with increased perioperative morbidity. This study investigated the factors influencing nutritional derangements in these patients. A series of 46 OJ patients were investigated prospectively (28 malignant tumors, 18 benign obstructions). A nutritional risk index of < 83.5 was used to define protein-calorie malnutrition. Liver function, cholecystokinin (CCK), tumor necrosis factor-alpha (TNFalpha), and endotoxin lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 33 publications
3
9
0
2
Order By: Relevance
“…Moreover, patients with severe jaundice and cholangitis were more hypoproteinaemic than those with mild disease ( Table 2). It has been reported that the severity of hypoproteinaemia seems to be associated with the intensity and duration of the jaundice and cholangitis (45). Biliary obstruction usually leads to moderate impairment of liver anabolic functions.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, patients with severe jaundice and cholangitis were more hypoproteinaemic than those with mild disease ( Table 2). It has been reported that the severity of hypoproteinaemia seems to be associated with the intensity and duration of the jaundice and cholangitis (45). Biliary obstruction usually leads to moderate impairment of liver anabolic functions.…”
Section: Discussionmentioning
confidence: 99%
“…ECW depletion in patients with biliary tract obstruction appears to be the final result of two antagonistic phenomena: negative water and sodium balances owing to inappropriate natriuresis and hypodipsia (probably mediated by increased ANP levels) on one hand, and a relative extracellular fluid expansion due to the effects of hypoalbuminaemia and weight loss on the other16.…”
Section: Discussionmentioning
confidence: 99%
“…Malnourishment is commonly seen in patients with an underlying illness such as cancer, or chronic organ failure [3,21,22,23,24,25,26,27,28]. For many years Albumin was of great interest for surgeons as an indicator of malnutrition.…”
Section: Nutritional Assessment and Population At Risk For Periopementioning
confidence: 99%